Chinese Medicines Induce Cell Death: The Molecular and Cellular Mechanisms for Cancer Therapy. (14th October 2014) - Wang, Xuanbin; Feng, Yibin; Wang, Ning; Cheung, Fan; Tan, Hor Yue; Zhong, Sen; Li, Charlie; Kobayashi, Seiichi
Abstract : Chinese medicines have long history in treating cancer. With the growing scientific evidence of biomedical researches and clinical trials in cancer therapy, they are increasingly accepted as a complementary and alternative treatment. One of the mechanisms is to induce cancer cell death. Aim . To comprehensively review the publications concerning cancer cell death induced by Chinese medicines in recent years and provide insights on anticancer drug discovery from Chinese medicines. Materials and Methods . Chinese medicines (including Chinese medicinal herbs, animal parts, and minerals) were used in the study. The key words including "cancer", "cell death", "apoptosis", "autophagy, " "necrosis, " and "Chinese medicine" were used in retrieval of related information from PubMed and other databases. Results . The cell death induced by Chinese medicines is described as apoptotic, autophagic, or necrotic cell death and other types with an emphasis on their mechanisms of anticancer action. The relationship among different types of cell death induced by Chinese medicines is critically reviewed and discussed. Conclusions . This review summarizes that CMs treatment could induce multiple pathways leading to cancer cell death, in which apoptosis is the dominant type. To apply these preclinical researches to clinic application will be a key issue in the future.